Rancang Bangun Sistem Digitalisasi Pengarsipan (E-SIP) Berbasis Website - Darusman, Calvin Dicky; Amaliyah; Dimisqiyani, Erindah (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
An organization can never be separated from administrative activities. Archivesare an activity that cannot be separated from administrative activities. Archives playan important role for organizations because archives are used to store and maintainimportant records or documents related to the organization's activities. Apart fromthat, archives also help organizations to avoid the risk of losing information ordocuments that could be considered valuable. By having well-organized archives,organizations will find it easier to access the information they need. In the past,archives were managed manually, such as notebooks and documents which werestill in the form of paper, which required storage space and required time in the search process. Therefore, nowadays many organizations choose to switch to digitalarchiving, which is an easier and faster process than manual archiving. Archivesmanagement at BRIDA East Java Province has not been carried out using a digitalsystem. To minimize risks in archival storage, it is better to change the manualrecords management system to a digital archive. The preparation of this finalassignment used qualitative research methods. Qualitative research usually collectsdata by conducting observations, interviews, and documenting research activities.Because archiving in BRIDA East Java Province is still done manually, in thisresearch a website-based design idea called Electronic Archives (E-SIP) wasdesigned to simplify the digital archiving process. With the creation of this design,it is hoped that it will facilitate the management of archives at BRIDA East JavaProvince and that archiving can be carried out digital.